2019
DOI: 10.3390/f10121157
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification and Characterization of Heat-Shock Transcription Factors in Rubber Tree

Abstract: Heat-shock transcription factors (Hsfs) play a pivotal role in the response of plants to various stresses. The present study aimed to characterize the Hsf genes in the rubber tree, a primary global source of natural rubber. In this study, 30 Hsf genes were identified in the rubber tree using genome-wide analysis. They possessed a structurally conserved DNA-binding domain and an oligomerization domain. On the basis of the length of the insert region between HR-A and HR-B in the oligomerization domain, the 30 me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…For example, AtHSFA7b positively regulates salt tolerance of chrysanthemum and Arabidopsis (Li et al, 2018;Zang et al, 2019). HbHsfA7a was significantly upregulated under low-temperature stress in the other hardy rubber (Li et al, 2019c). Promoter analysis also showed that A1 and A7 may participate in the regulation of development and abiotic stresses in B. juncea.…”
Section: Analysis Of the Expression Of Bjuhsf Genesmentioning
confidence: 96%
“…For example, AtHSFA7b positively regulates salt tolerance of chrysanthemum and Arabidopsis (Li et al, 2018;Zang et al, 2019). HbHsfA7a was significantly upregulated under low-temperature stress in the other hardy rubber (Li et al, 2019c). Promoter analysis also showed that A1 and A7 may participate in the regulation of development and abiotic stresses in B. juncea.…”
Section: Analysis Of the Expression Of Bjuhsf Genesmentioning
confidence: 96%
“…To analyse gene expression in four cold-tolerant rubber tree clones and four coldsensitive rubber tree clones, the treatment of the grafted plantlets was performed under cold stress in accordance with a published protocol [26]. Bark samples were collected from five plantlets of each rubber tree clone at 0 h, 4 h, 8 h, and 24 h of treatment and mixed as one sample.…”
Section: Stress Treatmentsmentioning
confidence: 99%
“…Quantitative real-time PCR (qPCR) was carried out with 2 ×TB Green TM Premix Ex Taq TM II (TliRNaseH Plus) (TaKaRa, Shiga, Japan) through the CFX384 Real-Time System (Bio-Rad, Herakles, CA, USA) according to the described protocol [26]. Each sample used three biological replicates, and each biological replicate used three technical replicates for qPCR analysis.…”
Section: Quantitative Expression Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…After 48 h, the plants were divided into five groups, each group containing 105 plantlets, that were exposed to different treatment conditions. According to our recent study ( Li et al, 2019 ), two groups of seedlings were transferred to 4 °C and 40 °C growth chambers for low- and high temperature treatments, respectively. One group of plantlets was removed from the nutritious bags and cultivatable soil, and bare roots were placed in flowerpots for drought stress treatment.…”
Section: Methodsmentioning
confidence: 99%